PENATALAKSANAAN AKUPUNTUR, TUINA CHUZHEN DAN FOOD TERAPY TCM TERHADAP HIPEREMISIS GRAVIDARUM - Agussalim, Wijono Sukaputra; Siahaan, Richard; Basuki, Rachmad; Maris, Stella (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2022)
Background : According to Mohtar (2012), predisposing factors, such as increased estrogen and HCG levels during pregnancy, primigravida, organic factors, endocrine factors, and psychological factors are the reasons of hyperemesis gravidarum. Loss of weight is a side effect of hypermesis gravidarum. (Varney, 2007). Chronic Energy Deficiency (KEK) in pregnant women will result from weight reduction in those who are pregnant. (Prawirohardjo, 2007). Traditional Chinese medicine is one non-pharmacological treatment option for pregnant women who suffer hyperemesis gravidarum. Objective: Understanding how successful TCM food therapy, acupuncture management, and tuina chuzhen are for treating hyperemesis gravidarum Method : The technique that involves giving patients or clients direct instruction or demonstration result : Acupuncture at PC6 Neiguan point is effective in reducing complaints of hyperemesis. Tuina Chuizen therapy at Bazhen point, Hechelu point on the head, and Back-Loin will gradually relax the muscles. Pregnant women with hyperemesis gravidarum can benefit from TCM-based food therapy by avoiding foods with strong odors. Suggestion : Patients with Heperemesis Gravidarum may benefit from traditional alternative therapy, but pregnant women continue to regularly visit their obstetrician to discuss the health of the mother and fetus. Keywords : Traditional Chinese Medicine, akupuntur, tuina chuzhen, and hyperemesis gravidarum